Pathways to Digital Service Innovation: The Role of Digital Transformation Strategies in Established Organizations - David Soto Setzke; Tobias Riasanow; Markus Böhm; Helmut Krcmar (Information Systems Frontiers, 2021)
Digital technologies are radically changing how established organizations design novel services. Digital transformation (DT) strategies are executed to manage the transition from product-centric to service-centric business models based on digital technologies. However, little is known about what configurations of DT strategies lead to successful digital service innovation (DSI) in established organizations. We employ fuzzy-set Qualitative Comparative Analysis on a set of 17 case studies of DT strategies from established organizations with different industry backgrounds. We identify several distinct configurations of DT strategies that lead to successful and unsuccessful DSI. Based on these configurations, we deduce that the threat of digital disruption negatively impacts an organization's innovation activities. Furthermore, we find that strategic partnerships can be leveraged by organizations that face an imminent threat of digital disruption while organizations with competitive advantages may rely on "do-it-yourself" approaches. Lastly, we find that the involvement of a C-level executive is a necessary requirement for successful DSI. Our results contribute to theory by integrating research on DSI and DT, providing a perspective on DSI failure, and employing a configurational research approach that allows us to highlight interdependencies between factors as well as insights into the individual factors. Furthermore, we provide actionable recommendations for executives.
Keywords: 000; Digital transformation; Digital service innovation; Radical service innovation; Digital transformation strategies; Qualitative comparative analysis